THE INFLUENCE OF TAX PLANNING AND PROFITABILITY ON COMPANY VALUE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2020-2023 - M. Tarmizi; Yuli Maylena; Sujeni, Sujeni; Diddo Adding Adove; Gilang Pranajasakti (Indragiri Research Center (ingreat), 2024)
This research aims to determine the effect of tax planning and profitability on company value in manufacturing companies listed on the Indonesian Stock Exchange by publishing financial reports and annual reports for the 2020-2023 period. The type of research used is quantitative research. The sampling technique is carried out using techniques purposive sampling. So the sample obtained was 60 manufacturing companies listed on the Indonesia Stock Exchange with a total of 60 companies observing data for 4 years of observation, namely 240 companies. This type of data source uses secondary data taken through website official www.idx.co.id. The data analysis technique used in this research is multiple linear regression analysis with tools software SPSS 23. The results of this study indicate that tax planning has no significant effect on company value and profitability has a significant effect on company value and tax planning and profitability together have a significant effect on company value.